2011
DOI: 10.21236/ada579910
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Thermal Remediation of DNAPL Source Zones

Abstract: Report Documentation PageForm Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…In past decades, various remediation technologies have been developed, involving individual units or combined physical, chemical and biological processes, such as air sparging [2], thermal treatment [3], enhanced-solubilization flushing [4], in situ bioremediation, and permeable reactive barriers (PRB) [5]. While each technology has met with success for certain applications, each of them has specific limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, various remediation technologies have been developed, involving individual units or combined physical, chemical and biological processes, such as air sparging [2], thermal treatment [3], enhanced-solubilization flushing [4], in situ bioremediation, and permeable reactive barriers (PRB) [5]. While each technology has met with success for certain applications, each of them has specific limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The total oxidant demand test was developed as a diagnostic tool to generally measure the mass of oxidant needed to significantly reduce background soil oxidant demand, improve contaminant oxidation, and to quantify how much oxidant is needed for ISCO design purposes. 35,36 Others have reported that repeated persulfate treatments did not improve the rate of contaminant oxidation in some soils and minerals. 33 One possible explanation for these seemingly opposing results may lie in the role of radical scavenging.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Radical scavenging involves the reaction between radicals and nontarget chemical species; and NPR involves reactions that do not yield radicals and consequently deplete the source of oxidants, such as persulfate (S 2 O 8 2− ) (PS) or hydrogen peroxide (H 2 O 2 ), which in turn diminishes radical production. PS reaction with natural media involves NPR [1][2][3][4][5] and contributes to treatment inefficiency. Radical scavengers may either be soluble in the aqueous phase or may be present as a solid phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-scale experiments in Oregon [JOHNSON, 2007] showed a marked reduction in liquidphase permeability at low temperatures of approx. 50°C as a result of the appearance of gas bubbles by ebullition (degassing).…”
Section: Phases Of Operationmentioning
confidence: 99%